AB1141 EVALUATION OF INFLUENZA AND PNEUMOCOCCAL VACCINATION RATES IN PATIENTS WITH RHEUMATOID ARTHRITIS AND SPONDYLOARTHRITIS, AND THE AWARENESS OF RHEUMATOLOGISTS ABOUT VACCINATION. (13th June 2020) - Kurut Aysin, İ. and Aysin, M. and Solmaz, D. and Baş Tomaş, N. and Koç, F. and Durak Ediboglu, E. and Kabadayi, G. and Gerçik, Ö. and Gucenmez, S. and Akar, S.
Abstract : Background: Patients with inflammatory arthritis have increased risk of infections which may lead to morbidity and mortality. Some of those infections could be prevented by vaccination. Objectives: The main objectives of the present study were to investigate (a) the uptake rate of influenza and pneumococcal vaccination among patients with rheumatoid arthritis (RA) and spondyloarthritis (SpA) attending a rheumatology outpatient clinic, (b) the factors associated with their vaccination rate and, (c) the attitudes of Turkish rheumatologists about vaccination. Methods: Patients, followed-up in a tertiary rheumatology outpatient clinic with the diagnosis of RA and SpA, volunteered for participating to study, were included in this cross-sectional study. Data regarding the socio-demographic and disease-related characteristics (including disease duration, medications used, and comorbid conditions) of the patients, vaccination history, the knowledge about the vaccination, and the factors potentially associated with the uptake of vaccination were collected by face-to-face interview using a standardized questionnaire. 102 out of 345 rheumatologists have participated in a web-based survey. Results: In total, we collected data from 387 patients (260 with SpA and 114 with RA; 204 [52.8%] female and mean age 46.6 ± 12.7 years). Only 123 (32.3%) of our patients were responded that their disease or treatment might be related to the increased risk for infectious diseases. Influenza and pneumococcal vaccines were administered to 71 (21.4%) and 21 (6.1%) patients, respectively. Vaccination for influenza was recommended by family physicians in 26 patients and by rheumatologists in 12 patients. Rate of influenza vaccination was significantly higher in patients >65 years (p=0.021) and with any co-morbid conditions (p=0.002). The main reasons reported by patients regarding not to be vaccination were (a) the belief that they did not need the vaccine (49.4% for influenza and 26.2% for pneumococcal vaccine), (b) the absence of recommendation from their physicians (24.1% for influenza and 26.2% for pneumococcal vaccine), (c) fear of adverse event of vaccination (28.8% for influenza and 3.2% for pneumococcal vaccine), and (d) lack of knowledge about vaccination (6.1% for influenza and 12.5% for pneumococcal vaccine). Even though 50% of rheumatologists who responded to the survey were aware of the presence of national vaccination recommendations, all of them stated that patients with inflammatory arthritis need to be vaccinated for both influenza and pneumococcal infections. Influenza and pneumococcal vaccines were administered to 23 (22.5%) and 4 (3.9%) rheumatologists, respectively. Conclusion: Although the knowledge and awareness about influenza and pneumococcal vaccinations were seemed to be high among rheumatologists, vaccination rates for both were insufficient in RA and SpA patients. There remains significant effort to improve vaccination rates and to prevent morbidity and mortality due to vaccine-preventable infections in inflammatory rheumatic diseases. References: [1]Van Assen S, Agmon-Levin N, Elkayam O, Cervera R, Doran MF, Dougados M, et al. EULAR recommendations for vaccination in adult patients with autoimmune inflammatory rheumatic diseases. Ann Rheum Dis 2011;70:414–22. [2]MTT Nguyen, H Lindegaard, O Hendricks & N Friis-Møller. Factors associated with influenza and pneumococcal vaccine uptake among rheumatoid arthritis patients in Denmark invited to participate in a pneumococcal vaccine trial (Immunovax_RA), Scandinavian Journal of Rheumatology 2017;1–8. Disclosure of Interests: None declared